Complex Care Program Enrollment and Change in ED and Hospital Visits from Medical Device Complications. Issue 5 (September 2021) - Barreda, Christina B.; Ehlenbach, Mary L.; Nackers, Allison; Kelly, Michelle M.; Shadman, Kristin A.; Sklansky, Daniel J.; Edmonson, M. Bruce; Zhao, Qianqian; Warner, Gemma; Coller, Ryan J.
Abstract : Introduction: Medical device-related complications often lead to emergency department (ED) visits and hospitalizations for children with medical complexity (CMC), and pediatric complex care programs may be one way to decrease unnecessary encounters. Methods: A retrospective cohort study comparing ED and inpatient encounters due to device complications of 2 cohorts of CMC at a single children's hospital during 2014–2016; 99 enrolled in a complex care program and 244 in a propensity-matched comparison group. Structured chart reviews identified ED and inpatient encounters due to device complications. The outcome was a change in the frequency of these encounters from the year before to the year after enrollment in the hospital's complex care program. Program effects were estimated with weighted difference-in-differences (DiDs), comparing the change in mean encounter frequency for CMC enrolled in the program with change for propensity-matched children not enrolled in the program. Results: Mean encounters related to device complications decreased for both groups. Complication-related ED encounters per year decreased from a weighted mean (SD) of 0.74 (0.85) to 0.30 (0.44) in enrolled children and 0.26 (0.89) to 0.12 (0.56) in comparison children, a DiD of 0.30 fewer [95% confidence interval (CI) −0.01 to 0.60]. The largest reductions in device complication ED visits were among those with enteral tubes [0.36 fewer (95% CI 0.04–0.68)]. Hospitalizations decreased over time, but DiDs were not significantly different between groups. Conclusions: Acute care use from device complications decreased with time. Complex care program enrollment may be associated with more substantial reductions in device complication ED visits, and effects may be most pronounced for CMC with enteral tubes.